Dengue Vaccine Development at the Dengue virus serotypes - Desi Irawati, Adinda; Salim, Hotimah Masdan (Jurnal Medis Islam Internasional, 2019)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus (DENV1-4) and is transmitted by the Aedes aegypti mosquito. However, in 2015, official data from the member countries, WHO reported more than 3.2 million cases, including 10,200 severe dengue cases and 1181 deaths. The protein encoded by the genome of dengue virus. Major structural and non structural proteins making up the genome of dengue. From genomic data several studies found that mechanism of vaccine that can use in dengue virus. Several vaccines was establish in the world for example Live attenuated Vaccine, Chimera Vaccine, Subunit Vaccine, DNA vaccines DENV, Activated DENV Vaccine - Whole Virus Particles, Activated DENV Vaccine - Recombinant Subunit DENV, and DENV Vaccine 5.